PERLINDUNGAN HUKUM BAGI LEANDER YANG MENGALAMI KREDIT MACET PADA LEMBAGA PEMBIAYAAN ONLINE/ELEKTRONIK DIKAITKAN DENGAN PRINSIP KEHATI-HATIAN - Melati, Fahra Agustina; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The geogarfic location of Indonesia which is an archipelago. Community outreach to banking services is difficult because banking itself is uneven. Banking services are only piled up in the city center, lacking in touch with people in remote areas. This has led to disparities in welfare in Indonesia due to uneven national economic development. Financing Institutions as another alternative financing, so that more flexible and moderate funding institutions are created from banks, which in certain cases the risk level is even higher, such as coin cooperatives with peer to peer lending models. The service provider is only a party that brings the leander and borrower together. Based on the Financial Services Authority Regulation No. 77 / POJK.01 / 2016 concerning Information Technology Lending and Borrowing Services and Financial Services Authority Regulation Number 13 / POJK.02 / 2018 concerning Digital Financial Innovation in the Financial Services Sector.This research is a research that uses a normative juridical approach, namely research that is focused on examining the application of legal norms or norms in positive law and with the type of library research (Library Research).The conclusion from the writing of this thesis is that the user in this case specifically the leander as the person with excess funds is more protected in carrying out all activities involving financial technology, lending and borrowing money so that the leander and borrower have a clear position in the Indonesian legal instrument in the legislation. And clearly the credit dispute resolution institutions authorized to resolve them.Keywords: Peer To Peer Lending, Legal Protection, OJK.